2019
DOI: 10.1051/0004-6361/201935609
|View full text |Cite
|
Sign up to set email alerts
|

The LOFAR Tied-Array All-Sky Survey (LOTAAS): Survey overview and initial pulsar discoveries

Abstract: We present an overview of the LOFAR Tied-Array All-Sky Survey (LOTAAS) for radio pulsars and fast transients. The survey uses the high-band antennas of the LOFAR Superterp, the dense inner part of the LOFAR core, to survey the northern sky (δ > 0 • ) at a central observing frequency of 135 MHz. A total of 219 tied-array beams (coherent summation of station signals, covering 12 square degrees), as well as three incoherent beams (covering 67 square degrees) are formed in each survey pointing. For each of the 222… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 105 publications
5
138
0
Order By: Relevance
“…We are using this telescope in the frequency range 119 − 151 MHz to perform the LO-FAR Tied-Array All-Sky Survey (LOTAAS, Coenen et al 2014) 2 for pulsars and fast transients in the Northern sky. A detailed description of the survey is presented in Sanidas et al (2019). Among the LOTAAS discoveries presented in this paper, PSR J0815+4611 has been first presented by Jelić et al (2015), who identified a steep spectrum, unresolved and polarized point source in continuum images of the 3C 196 field observed by the LOFAR Epoch of Reionization project (Candi2, Ger de Bruyn, priv.…”
Section: Introductionmentioning
confidence: 97%
“…We are using this telescope in the frequency range 119 − 151 MHz to perform the LO-FAR Tied-Array All-Sky Survey (LOTAAS, Coenen et al 2014) 2 for pulsars and fast transients in the Northern sky. A detailed description of the survey is presented in Sanidas et al (2019). Among the LOTAAS discoveries presented in this paper, PSR J0815+4611 has been first presented by Jelić et al (2015), who identified a steep spectrum, unresolved and polarized point source in continuum images of the 3C 196 field observed by the LOFAR Epoch of Reionization project (Candi2, Ger de Bruyn, priv.…”
Section: Introductionmentioning
confidence: 97%
“…Such parent populations can be used to optimise the strategies for such pulsar surveys as using LOFAR (van Leeuwen & Stappers 2010) and the Square Kilometre Array (SKA; Smits et al 2009), and predict the outcomes to within a factor of a few (cf. Sanidas et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All data were blindly searched on the Dutch supercomputer Cartesius. We used the LOTAAS single-pulse search pipeline (Sanidas et al, 2019), which is based on PRESTO, to remove RFI and identify individual pulses up to widths of 100 ms. We inspected the single-pulse and periodic output both by eye, and with the LOTAAS single-pulse (Michilli & Hessels, 2018;Michilli et al, 2018) and periodic (Lyon et al, 2016) No single pulses were found that appeared in both the initial search of the 50−60 pc cm −3 dispersion-measure range, and the full search. Of the noteworthy periodic candidates seen in the 2011 data (cf.…”
Section: Observationsmentioning
confidence: 99%